HASIL KALI TENSOR ALJABAR-C* - Hariadi, Nora
Abstract : Learning C*-algebra, we often faced problems to make new C*-algebra from the old one. New C*-algebra could be obtained by tensor pro-ducts. This thesis will discuss how to construct C*-algebra tensor products, where its algebraic property of tensor products and Cs-algebra\'s norm property are still fulfilled. Because of C*-algebra\'s norm property, tensor products from two C*-algebras will produce more than one new C*-algebras. However, there is one class in C*-algebra which its tensor product with any other C*-algebra will only produce one new C*algebra. This class known as nuclear C*-algebra.